Cell wall-associated transition metals improve alkaline-oxidative pretreatment in diverse hardwoods. Issue 5 (29th October 2015) - Bansal, Namita; Bhalla, Aditya; Pattathil, Sivakumar; Adelman, Sara L.; Hahn, Michael G.; Hodge, David B.; Hegg, Eric L.
Abstract : Cell wall-associated, redox-active transition metals play a critical role in the efficacy of oxidative delignification. Abstract : The responses of four diverse hardwoods (hybrid poplar, silver birch, hybrid aspen, and sugar maple) to alkaline hydrogen peroxide (AHP) pretreated at ambient temperature and pressure were analyzed to gain a deeper understanding of the cell wall properties that contribute to differences in enzymatic hydrolysis efficacy following alkaline-oxidative pretreatment. The enzymatic hydrolysis yields of these diverse hardwoods increased significantly with increasing the cell wall-associated, redox-active transition metal content. These increases in hydrolysis yields were directly correlated with improved delignification. Furthermore, we demonstrated that these improvements in hydrolysis yields could be achieved either through elevated levels of naturally-occurring metals, namely Cu, Fe, and Mn, or by the addition of a homogeneous transition metal catalyst ( e.g. Cu 2, 2′-bipyridine complexes) capable of penetrating into the cell wall matrix. Removal of naturally-occurring cell wall-associated transition metals by chelation resulted in substantial decreases in the hydrolysis yields following AHP pretreatment, while re-addition of metals in the form of Cu 2, 2′-bipyridine complexes and to a limited extent Fe 2, 2′-bipyridine complexes prior to pretreatment restored the improved hydrolysis yields. Glycome profiles showed improved extractability of xylan, xyloglucan, and pectin epitopes with increasing hydrolysis yields for the diverse hardwoods subjected to the alkaline-oxidative pretreatment, demonstrating that the strength of association between cell wall matrix polymers decreased as a consequence of improved delignification.